(untitled) (Research, Society and Development, 2020)
Sodium (Na) is considered a beneficial element for plants in general and, for table beet some other crops, it can partially replace potassium (K) in some functions in the plant. However, little is known in respect to the influence of this cation on table beet. In this context, the present study aimed to verify the response of nutrition with Na in substitution and in addition to nutrition with K on the growth and nutrition of the table beet. The experiment, conducted in vases with nutrient solution in a completely randomized design, was made up of three replications and seven treatments: T1 (100% K e 0 % Na), T2 (75% K e 25% Na) , T3 (50% K e 50% Na), T4 (25 % K e 75% Na), T5 (0% K e 100 % Na), T6 (100% K e 25 % Na) e T7 (100 K e 50 % Na). The results showed that the substitution of the potassium by the sodium in 25% of the recommended base and addition of Na (25 and 50%) to the nutrient solution with 100% K did not interfere significantly in the growth of the plants. The sodium uptake by the table beet was lower in comparison with that of potassium. Besides, the presence of Na affected the levels of other nutrients. Thus, it was concluded that table beet produces satisfactorily under regular applications of K with the addition of Na, as well as when partially replacing the potassium at the level of 25% of Na provided in the culture solution.